PENGARUH PEMBERIAN TUGAS RUMAH DAN PETA KONSEP TERHADAP HASIL BELAJAR BIOLOGI KELAS VII SMP NEGERI 22 PADANG - Karlinda, Delvita; Nurhadi, Nurhadi; Nursyahra, Nursyahra (STKIP PGRI Sumbar, 2014)
There are many problems that occur in the learning process, one of them is low of biological learning outcomes among biology students because of learning process that is still dominated by the teacher. Most students are lazy to read the subject matter being studied. This cause the outcomes of student biology learning are relatively low and below the minimum completeness criteria (KKM), that is 75. The purpose of this observation was to determine the Effect of Granting Homework and Concept Map for the Result of Biology Learning of Grade VII Padang Public Junior High School 22. This research is an experimental with research design is Randomized Control Group Posstest Only Design. This research was conducted at Padang Public Junior High School 22 second term of VII grade in January-March listed on the academic year2013/2014. Population in this research are all of Grade VII students listed on the acade mic year2013/2014 consist of 8 classes. Sampling using purposive sampling method and obtained VII3 grade as the experimental class and VII5 grade as the control class. The instrument used is written in the form of an objective test. Based on the achievement test scores of biology, experiment class obtained 78,23 and the average control class is 72,67. Form the t-test analysis, tcount value of (1,80)> ttable ( 1,67) which means that H1 is accepted. It can be concluded that granting homework andconcept map can be improve learning outcomes biology of VII grade in SMP N 22 Padang onecosystem material.